Diagnosis, Pathophysiology and Experimental Models of Chronic Lung Allograft Rejection - Gauthier, Jason M. (Transplantation, 2018)
Chronic rejection is the Achilles’ heel of modern lung transplantation, characterized by a slow, progressive decline in allograft function. Clinically, this manifests as obstructive disease, restrictive disease, or a mixture of the 2 depending on the underlying pathology. The 2 major phenotypes of chronic rejection include bronchiolitis obliterans syndrome and restrictive allograft syndrome. The last decade of research has revealed that each of these phenotypes has a unique underlying pathophysiology which may require a distinct treatment regimen for optimal control. Insights into the intricate alloimmune pathways contributing to chronic rejection have been gained from both large and small animal models, suggesting directions for future research. In this review, we explore the pathological hallmarks of chronic rejection, recent insights gained from both clinical and basic science research, and the current state of animal models of chronic lung rejection.